Bronchopulmonary dysplasia patients have preserved CT-measured central airway luminal area. (August 2020) - Guo, Winston L.; Eli, Ilhan M.; Ripoll, Juan G.; Baker, Sarah E.; Shepherd, John R.A.; Wiggins, Chad C.; Welch, Brian T.; Joyner, Michael J.; Dominelli, Paolo B.
Abstract: Bronchopulmonary dysplasia (BPD) is a condition of neonatal chronic lung disease due to disruption or dysregulation of pulmonary development. However, the pathophysiology of BPD in the larger conducting airways is not yet fully understood. The objective of our study was to determine if the area of the central airways are altered in patients with a history of BPD. We hypothesized that compared to age- and sex-matched controls, BPD patients would have decreased area of the central conducting airways. Twenty-two BPD patients (n = 10 male, n = 12 female; median age = 10 [range:1–49] yrs) and n = 22 matched controls (n = 10 male, n = 12 female; median age = 10 [range:1–48] yrs) who had undergone a chest computed tomography (CT) scan were retrospectively identified. Measurement and analysis was performed using software that reconstructs the airways into 3D. Measurements of airway area were conducted at three points based on anatomic bifurcations for each of the following structures: trachea, left main bronchus, left upper lobe, left lower lobe, right main bronchus, intermediate bronchus, and right upper lobe. The luminal area for each airway was calculated based on the averages of the three measures. Airway luminal area was not different between BPD patients and matched controls for any of the measured airways (p > 0.05). Total lung volume detected in the CT scans was not different between BPD patients and matched controls (median [range]; 2775 [522–6215] vs 2969 [851–5612] cm 3, p > 0.05). Our results suggest the luminal areas of the large conducting airways in patients with BPD are not different from matched controls. Highlights: The pathophysiology of large airways in Bronchopulmonary dysplasia (BPD) is unclear. CT derived measures of central airways luminal area in BPD patients. Large conducting airways in patients with BPD are not different from controls.